Особливості міжкультурної комунікації та подолання лінгвоетнічного бар’єру у студентів на заняттях з практики перекладу - Даніленко, Анастасія Юріївна; Карачова, Дар'я Володимирівна (Луганський національний університет імені Тараса Шевченка, 2019)
У статті розглянуто поняття міжкультурної комунікації як засобу досягнення ефективної взаємодії між студентами-іноземцями та українськими студентами філологічних спеціальностей під час занять з англійської мови. Проведено аналіз результатів дослідження щодо особливостей міжкультурної комунікації між студентами українцями та закордонними студентами у процесі опрацювання матеріалу на заняттях з практики перекладу. Розглянуто шляхи подолання лінгвоетнічних бар'єрів та проаналізовано потенційні причини їх появи. На сучасному етапі розвитку суспільства та за умов глобалізованого процесу комунікації питання успішності міжкультурної взаємодії набуває все більшої популярності та нових стратегій вивчення. Сьогодні ця проблема відіграє вирішальну роль, адже культура поведінки та культурні особливості значним чином впливають на якість перекладу, адже це закладене на психологічному рівні та характеризує манеру та стиль поведінки.

В статье рассмотрено понятие межкультурной коммуникации как средства достижения эффективного взаимодействия между студентами иностранцами и украинскими студентами филологических специальностей во время занятий по английскому языку. Проведен анализ результатов исследования особенностей межкультурной коммуникации между украинскими и зарубежными студентами в процессе обработки материала на занятиях по практике перевода. Рассмотрены пути преодоления лингвоэтнических барьеров и проанализированы потенциальные причины их появления. На современном этапе развития общества и в условиях глобализационного процесса коммуникации вопросы успешности межкультурного взаимодействия приобретает все большую популярность и новые стратегии изучения. Сегодня эта проблема играет решающую роль, ведь культура поведения и культурные особенности значительным образом влияют на качество перевода, ведь это заложено на психологическом уровне и характеризует манеру и стиль поведения.

The article deals with the concept of intercultural communication as a means of achieving effective interaction between foreign and Ukrainian students of philological specialties during classes in English language. The analysis of the results of the study of the features of intercultural communication between Ukrainian and foreign students in the course of study process in the classroom during the course of translation has been carried out. Ways of overcoming the language and ethnic barriers are considered and potential causes of their appearance are analyzed. At the present stage of development of society and in the context of the globalization process of communication, issues of successful intercultural interaction is becoming increasingly popular and new learning strategies are appearing. Today this problem is crucial, because the culture of behavior and cultural characteristics significantly affect the quality of translation, as it is based on psychological peculiarities of human mind and characterizes the manner and style of behavior. Communication between representatives of different cultures and nations should bring mutual benefit to all participants in the interaction situation. The research of this topic is extremely popular nowadays as there are a lot of foreign students who study in our country that is why we need to guarantee the quality of communication for them during their study.
Особенности межкультурной коммуникации и преодоления лингвоэтнического барьера у студентов на занятиях по практике перевода
Features of intercultural communication and overcoming the language and ethnic barriers among students during the course of translation
Keywords: міжкультурна комунікація; лінгвоетнічний бар'єр; переклад; взаємодія; межкультурная коммуникация; лингвоэтнический барьер; перевод; взаимодействие; intercultural communication; language and ethnic barriers; translation; interaction